Pembentukan Karakter Berbasis Potensi Diri Melalui Pendidikan Islam di SMKN Rejang Lebong - Fasyiransyah, Fasyiransyah; Filenti, Elkin; Yuhmir, Yuhmir; Karti, Aisyah (Belajea: Jurnal Pendidikan Islam, 2024)
This study aims to describe the formation of character based on self-potential through Islamic education for students at SMKN Â Rejang Lebong. And through the application of this character education can shape the character of students who are Islamic and tolerant. The method used in this research is a qualitative method with a descriptive qualitative approach. Determination of informants/respondents using a purposive sampling technique, namely sampling data sources with certain considerations. Data collection techniques used in this study are observation, in-depth interviews, and documentation. The results of the study found that the formation of self-potential-based character through Islamic education at SMKN Â Rejang Lebong was very well implemented, although not one hundred percent, where the teacher had carried out his duties as a teacher, as a motivator and as an evaluator and provided character values based on self-potential through education Islam, creates a religious educational environment both in learning and outside learning when carrying out extra-school activities.